Coronary Calcification and Plaque Vulnerability: An Optical Coherence Tomographic Study. (January 2016) - Ong, Daniel S.; Lee, Jay S.; Soeda, Tsunenari; Higuma, Takumi; Minami, Yoshiyasu; Wang, Zhao; Lee, Hang; Yokoyama, Hiroaki; Yokota, Takashi; Okumura, Ken; Jang, Ik-Kyung
Abstract : Background—: Spotty superficial calcium deposits have been implicated in plaque vulnerability based on previous intravascular imaging studies. Biomechanical models suggest that microcalcifications between 5 and 65 µm in diameter can intensify fibrous cap stress, promoting plaque rupture. However, the 100- to 200-µm resolution of intravascular ultrasound limits its ability to discriminate single calcium deposits from clusters of smaller deposits, and a previous optical coherence tomographic investigation evaluated calcifications within a long segment of artery, which may not truly reflect the mechanics involved in potentiating focal plaque rupture. Methods and Results—: Detailed optical coherence tomographic assessment of coronary calcification at the culprit plaque (10-mm length) was performed in 53 patients with acute ST-segment–elevation myocardial infarction mediated by plaque rupture and 55 patients with stable angina pectoris. The number and longitudinal length of individual calcium deposits were recorded. Cross-sectional images were analyzed every 1 mm for calcium arc and depth, and these quantitative parameters were used to define individual deposits as spotty, large, and superficial. There was no significant difference between ST-segment–elevation myocardial infarction mediated by plaque rupture and stable angina pectoris groups in the number of total ( P =0.58), spotty ( P =0.87), or large calcium deposits ( P =0.27). Minimum calcium depth was similar between groups ( P =0.27), as was the number of superficial deposits ( P =0.35 using a 65-µm depth threshold and P =0.84 using a 100-µm depth threshold). Conclusions—: The number and pattern of culprit plaque calcifications did not differ between patients presenting with ST-segment–elevation myocardial infarction mediated by plaque rupture versus stable angina pectoris. The optical coherence tomographic assessment of coronary calcification may not be a useful marker of local plaque vulnerability as previously suspected. Registration Information—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01110538. Abstract : Supplemental Digital Content is available in the text.